1989
DOI: 10.1111/j.1471-0528.1989.tb03388.x
|View full text |Cite
|
Sign up to set email alerts
|

Virilizing nodular ovarian stromal hyperthecosis, diabetes mellitus and insulin resistance in a postmenopausal woman. Case report

Abstract: A 69-year-old woman (gravida 2, para 2) was referred with a 15-year history of progressive hirsutism. She shaved on alternite days and had scvcre fronto-temporal balding. Her menarche had been at 13 years, with an uneventful menopause at SO years of age. Non-insulin-dependent diabetes mellitus (NIDDM) had been diagnoscd 2 years before presentation and was well controlled with gliclazide and diet therapy. There was no family history of diabctcs or hirsutism.She was thin and had scvere frontal and teniporal bald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
1
14
0
3
Order By: Relevance
“…It is generally agreed that thecomas are benign although most of them are solid. Nonmalignant disorders usually follow a more slowly progressive benign course, as compared with the rapid progressive virilization seen with underlying malignancy 9. It has been suggested that a simple clinical assessment and a single serum testosterone measurement may be sufficient to differentiate between benign and malignant virilizing tumors in women presenting with hirsutism and androgenetic features 10.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that thecomas are benign although most of them are solid. Nonmalignant disorders usually follow a more slowly progressive benign course, as compared with the rapid progressive virilization seen with underlying malignancy 9. It has been suggested that a simple clinical assessment and a single serum testosterone measurement may be sufficient to differentiate between benign and malignant virilizing tumors in women presenting with hirsutism and androgenetic features 10.…”
Section: Discussionmentioning
confidence: 99%
“…3 Another case of postmenopausal hyperthecosis with type 2 diabetes reported improvement of HbA1c following oophorectomy, from 10.1% to 8.2%, which required cessation of gliclazide due to hypoglycaemia. 2 More data are available in patients with PCOS, which is associated with increased androgens (albeit at lower levels), and insulin resistance. Studies of the treatment of PCOS with anti-androgen therapies are however contradictory, often depending on the exact agent used, demonstrating improvement, no change and worsening of hyperinsulinism.…”
Section: Discussionmentioning
confidence: 99%
“…1 Improvement of diabetic control in hyperthecosis has been reported following oophorectomy, perhaps secondary to normalisation of the hyperandrogenaemia. 2 This is a report of worsening diabetes following oophorectomy. The case and possible explanations for the response are described.…”
Section: Introductionmentioning
confidence: 99%
“…the crystalloid-nega tive lutein cell mimicking the theca interna, the crystal loid-positive Leydig cell and the adrenocortical cell [22], Like its relative, the hilus cell, this highly steroidogenic cell is affected by hyperplasia and neoplasia. Diffuse, focal or nodular hyperplasia of the crystalloid-negative and crystalloid-positive steroid cell gives rise to hyperthecosis [ 1,[15][16][17] and stromal Leydig cell hyperplasia [5,6], respectively. These two androgenic states are only distin guished by the presence or absence of Reinke crystalloids and can be primary or secondary to a variety of primary or metastatic ovarian tumors [9], Primary neoplasms of these steroid cells, which used to be called lipid or lipoid cell tumors, are now classified according to their morphologic and functional expression [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal hyperandrogenism with overt clinical manifestations is rare and often related to an assortment of ovarian disorders including: (1) primary sex-cord-stromal tumors, steroid cell (lipoid cell) tumors [1][2][3], stromal luteomas [4], luteinized thecomas [5], Sertoli-Leydig tu mors or androblastomas [6], intraovarian Leydig cell tumors [7,8] and cystic granulosa cell tumors [9]; (2) tu mors of the extraovarian hilus cells [10][11][12]; (3) primary ovarian tumors with reactive stromal hyperplasia [13][14][15][16]; (4) secondary ovarian tumors with reactive stromal hyperplasia [17,18]; (5) hyperplastic states, stromal hy- testosterone 5.500 ng/dl (normal 15-52); androstenedione 600 ng/dl (normal 85-290); estradiol 163pg/ml (normal 10-50); normal DHEA levels; hemoglobin 18.6 g/dl. She had a total abdominal hys terectomy and bilateral salpingo-oophorectomy followed by rapid normalization of androgen levels and slow regression of her viriliza tion.…”
Section: Introductionmentioning
confidence: 99%